People treat social robots as real social agents - Eng, Alexander; Chi, Yam Kai; Gray, Kurt (The Behavioral and brain sciences, 2023)
When people interact with social robots, they treat them as real social agents. How people depict robots is fun to consider, but when people are confronted with embodied entities that move and talk – whether humans or robots – they interact with them as authentic social agents with minds, and not as mere representations.